Textile and machine learning: A Bibliometric analysis (Innovation & Development in Engineering and Applied Science, 2024)
Abstract. In the present research, a bibliometric analysis of scientific publications in the area of textile sciences from the area of machine learning is carried out. The search equation identifies as keywords (i) textile and (ii) machine learning from the scopus database, obtaining as initial result 308 publications, being 281 the final publications to be studied from 1991 to 2022. The bibliometric analysis was carried out using bibliometrix and VOS Viewer, showing the growing interest of the scientific community and authors in this area of research.
Keywords: textile; machine learning; bibliometric analysis; bibliometrix; VosViewer